2019
DOI: 10.3390/cancers11020129
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the Use of Cannabinoids in Oncology and Palliative Care Practice: A Review of the Evidence

Abstract: There is an increased interest in the use of cannabinoids in the treatment of symptoms in cancer and palliative care patients. Their multimodal action, in spite of limited efficacy, may make them an attractive alternative, particularly in patients with multiple concomitant symptoms of mild and moderate intensity. There is evidence to indicate cannabis in the treatment of pain, spasticity, seizures, sleep disorders, nausea and vomiting, and Tourette syndrome. Although the effectiveness of cannabinoids is limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 88 publications
0
27
0
1
Order By: Relevance
“…Despite the lack of robust evidence, the use of cannabis as a palliative treatment to relieve the side effects of drugs used in a range of medical conditions has been approved or is under consideration in many countries around the world and assumed to be safe [ 2 ]. Cannabis is particularly prevalent as a palliative treatment in oncology [ 2 , 3 , 4 , 5 ] to alleviate cancer symptoms, including nausea, anorexia, and cancer-related pain [ 6 ], despite the limited number of randomized clinical trials. Although the anti-inflammatory effects of cannabis and phytocannabinoids have long been known [ 7 , 8 ], the secondary effect of cannabis on the immune system has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of robust evidence, the use of cannabis as a palliative treatment to relieve the side effects of drugs used in a range of medical conditions has been approved or is under consideration in many countries around the world and assumed to be safe [ 2 ]. Cannabis is particularly prevalent as a palliative treatment in oncology [ 2 , 3 , 4 , 5 ] to alleviate cancer symptoms, including nausea, anorexia, and cancer-related pain [ 6 ], despite the limited number of randomized clinical trials. Although the anti-inflammatory effects of cannabis and phytocannabinoids have long been known [ 7 , 8 ], the secondary effect of cannabis on the immune system has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabinoids are analgesic and thus have been proposed to replace or supplement opioids for pain relief, especially in palliative care. 13 However, analgesic tolerance to exogenous CB 1 R agonists after repeated administration, due to CB 1 R desensitization is commonly encountered in preclinical models, 10,20,37 as also seen for opioids. Analgesic tolerance may contribute to the variable efficacy seen in meta-analyses of the use of cannabinoids for relieving chronic noncancer pain.…”
Section: Analgesic Tolerance To Cannabinoidsmentioning
confidence: 99%
“…Recent systematic reviews have shown the increasing interest of cannabis in medical use due to its multimodal action and the lack of negative effects that opioids carry 37 ; however, a recent meta-synthesis concluded that for adults with advanced cancer, there was no difference between cannabinoids and placebo in pain scores and that cannabinoids had a higher risk of adverse events compared to placebo 38 . Importantly, there are alternatives to consider as part of the pain management approach in palliative care that address the non-nociceptive, psychosocial, and spiritual dimensions of pain in palliative care that are opioid insensitive with supportive psychotherapy as part of the provision of palliative care 37,38 .…”
Section: Discussionmentioning
confidence: 99%